A Global Obstacle-Avoidance Map for Anthropomorphic Arms. (31st July 2014) - Fang, Cheng; Ding, Xilun
More and more humanoid robots are used in human society, and they face a wide variety of complicated manipulation tasks, which are mainly to be achieved by their anthropomorphic arms. Obstacle avoidance for the anthropomorphic arm must be a fundamental consideration to guarantee the successful implementation of these tasks. Different from traditional methods searching for feasible or optimal collision-free solutions for the anthropomorphic arm, a global obstacle-avoidance map for the whole arm is proposed to indicate the complete set of feasible solutions. In this map, the motion of the arm can be appropriately planned to intuitively control the configuration of the arm in motion. First, the cubic spline function is adopted to interpolate some well-chosen path points to generate a smooth collision-free path for the wrist of the anthropomorphic arm. Second, based on the path function of the wrist, the time and the self-rotation angle of the arm about the "shoulder-wrist" axis are used to parameterize all possible configurations of the arm so that a global two-dimensional map considering the obstacle avoidance can be established. Subsequently, a collision-free self-rotation angle profile of the arm can be well planned. Finally, the joint trajectories of a specific anthropomorphic arm, which correspond to the planned path of the wrist and self-rotation angle profile of the arm, can be solved on the basis of the general kinematic analysis of the anthropomorphic arm, and the specific structure. Several simulations are conducted to verify that the proposed collision-free motion planning method for anthropomorphic arms has some advantages and can be regarded as a convenient and intuitive tool to control the configuration of the anthropomorphic arm in motion, without collision with obstacles in its surroundings.